Synthesis and study of superacid ZrO–SiO–AlO mixed oxide - Olena Inshina; Alexander Korduban; German Tel'biz; Volodymyr Brei (Adsorption Science & Technology)
Strongly acidic ZrO 2 –SiO 2 –Al 2 O 3 mixed oxide with different Zr:Si:Al ratios have been synthesized by sol–gel method. It was found that superacid ( H 0  = −14.52) sites are formed at 12 ≤ Zr 4+  ≤ 39, 48 ≤ Si 4+  ≤ 72, 3 ≤ Al 3+  ≤ 31 at.%. According to the infrared spectra of adsorbed pyridine and acetonitrile-D 3 , acidic B- and strong L-sites are present on ZrO 2 –SiO 2 –Al 2 O 3 surface. Observed high-energy shift of Zr 3 d 5/2 peak in the X-ray photoelectron spectrum and low-field shift of 29 Si nuclear magnetic resonance signal of superacid Zr 35 Si 53 Al 12 oxide indicate that the electron density transfers from zirconium to silicon atom. The generation of superacidity in ZrO 2 –SiO 2 –Al 2 O 3 matrix could be explained by formation of coordinatively unsaturated Zr 4+ ions which are strong L-sites. It was shown that superacid ZrO 2 –SiO 2 –Al 2 O 3 efficiently catalyzes polymerization of tetrahydrofuran in the presence of acetic anhydride at 40℃ with 68% yield of polytetramethyleneoxide acetate.